Exploring the Impact of Female Leadership, Company Size, and Age on Financial Performance in Indonesia's Real Estate and Property Industry - Jamil, Poppy Camenia; M. Nur, Nuriman; Sianturi, Risma Silviani Meri (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to determine and analyze the positive and significant influence of female directors, company size, and company age on financial performance in the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2023. The study uses data from companies selected through purposive sampling based on specific criteria, namely property and real estate companies listed on the IDX during this period. The data analysis technique used is Multiple Linear Regression to examine the relationship between independent variables (female directors, company size, and company age) and the dependent variable (company financial performance). The results of this study are expected to provide insights into how these factors affect the financial performance of companies in the property and real estate sector, and contribute to a deeper understanding of the role of gender, company size, and age in the context of sustaining financial performance in the Indonesian capital market.